Eubacterial populations in the apple snail’s digestive gland - Dell Agnola, Federico Agustín (2024)
BACKGROUND: the invasive gastropod Pomacea canaliculata hosts bacterial endosymbionts in the gut. Here, we described the taxonomy and phylogeny of the bacterial biodiversity residing in the digestive gland (DG) and then highlight the metabolic characteristics of these microorganisms and their potential involvement in the host´s digestive physiology. RESULTS: a library of symbiotic 16S rDNA genes was built and analysed in silico. The sequences were classified into seven bacterial phyla: Bacillota, Pseudomonadota, Thermodesulfobacteriota, Bacteroidota, Chlorobiota, Chloroflexota, and Verrucomicrobiota. It was defined 26 Operational Taxonomic Units at 97% of genetic distance. Rarefaction curves and ecological indices showed that the DG bacterial community was diverse but non-evenness, with Lachnospiraceae and Azonexaceae as dominant OTUs. Most eubacterial OTUs were strict or facultative anaerobes, capable of digesting dietary β-polysaccharides, such as cellulose and chitin, and proteins (65%). Moreover, some of these bacteria would reduce metals (over 50%) and fix nitrogen (37%). Other OTUs were lactic acid-producing bacteria (40%) and/or short-chain fatty acids-producing bacteria (SCFAs Clostridium-like; 35%), sulphate-reducing bacteria (38%) and perchlorate-reducing bacteria (17%). CONCLUSION: this bacterial community may be beneficial for the host as it potentially would enhance macronutrient extracellular digestion, inorganic nitrogen assimilation, and aquatic xenobiotics detoxification.